Tsunami Disaster Preparedness Among School Community: New Evidence From Emerging Country - Haryani; Ezra Aditia; Friska Seftiyani; Rini Asmariati; Listy Vermana (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study evaluates the tsunami preparedness levels of six schools in Nagari Kataping, Padang Pariaman Regency, West Sumatra—one of the world's most vulnerable regions. A quantitative survey was conducted involving 160 respondents, including students, teachers, and principals. Preparedness was assessed based on five parameters: knowledge and attitudes, policies and guidelines, emergency response plans, early warning systems, and resource mobilization. Non-parametric tests (Kruskal–Wallis and Mann–Whitney U) were used to analyze significant variations in preparedness among the schools, with overall scores ranging from "not ready" to "ready." The results showed that teachers had higher preparedness scores compared to students and principals, while male students demonstrated slightly better preparedness than females. The parameters for knowledge and attitudes and emergency response plans were relatively strong, whereas early warning systems and resource mobilization were weak. Theoretically, this study extends the Disaster Risk Reduction (DRR) framework by introducing a preparedness index that captures intra-school variations based on roles, demographics, and institutional capacity. Practically, the findings provide recommendations for integrating DRR into curricula, strengthening school leadership, and increasing investment in early warning systems. Policy implications emphasize the importance of safe school programs and gender-sensitive disaster education in rural areas.